The Influence Of Customer Experience, Brand Image, And Social Media Influencer On Purchase Decision Of Staccato Products At Sunplaza Medan - Cyndi Varelie; Dewi Nurmasari Pane; Muhammad Dharma Tuah Putra Nasution (Journal of Management, Economic, and Accounting, 2026)
This research was conducted with the aim of determining the influence of customer experience, brand image, and social media influencer on the purchasing decision of Staccato products at Sunplaza Medan. The research method used in this study is descriptive quantitative. The population used in this study is consumers who buy Staccato products at SunPlaza. The sampling in this study was taken by selecting 10 (ten) consumers who have bought Staccato products every day for 10 days of research, so the sample size obtained is 100 consumers. The results of this study indicate that simultaneously customer experience, brand image, and social media influencer have a positive and significant effect on the purchasing decision of Staccato products at Sunplaza Medan.